2023
DOI: 10.1002/asia.202201130
|View full text |Cite
|
Sign up to set email alerts
|

Overall Improvement in Dielectric, Water Resistance and Mechanical Properties of Polyimide Film via Synergy between GO and Sandwich‐type Porous Structure

Abstract: Simultaneous improvement in dielectric, water resistance and mechanical properties of polyimide (PI) films is critical for their practical use, but difficult to achieve. Herein, a sandwich‐type porous GO/PI film with excellent comprehensive properties was obtained through integrating a GO‐containing complex, fluorine‐containing porous structure and sandwich‐type distribution of porous structure by a simple, low‐cost and green breath figure method. With the addition of only a small amount of GO‐containing compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 38 publications
(48 reference statements)
2
7
0
Order By: Relevance
“…At the equilibrium, the absorption ratios for PMDA–ODA and BPDA–PDA were 2.7% and 2.5%, respectively. These values were in good agreement with the literature value of PMDA–ODA (=2.51%) [ 11 ]. The relatively high water absorption of PIs is due to the hydrogen bonding of the BI (benzimidazole imide) ring.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…At the equilibrium, the absorption ratios for PMDA–ODA and BPDA–PDA were 2.7% and 2.5%, respectively. These values were in good agreement with the literature value of PMDA–ODA (=2.51%) [ 11 ]. The relatively high water absorption of PIs is due to the hydrogen bonding of the BI (benzimidazole imide) ring.…”
Section: Resultssupporting
confidence: 92%
“…The dielectric constants for dried films of PMDA–ODA, BPDA–PDA, and PET were 3.2, 3.0, and 3.3, respectively. These values were in good agreement with the literature values of 2.94 for PI [ 14 ], 2.9–3.9 for PMDA–ODA [ 11 , 12 , 13 , 26 ], 3.1 for BPDA–PDA [ 12 ], and 3.4 for PET [ 49 ]. The dielectric constants for PMDA–ODA and BPDA–PDA increased with the absorption time and became constant at around 180 min.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…When the GO content was 0.5 wt.% and the UV irradiation time was 900 s, the dielectric constant and dielectric loss of the composite film reached the lowest, which were 2.58 and 0.026 at 10 MHz, respectively, due to the confined electronic polarization caused by the crosslinked structure. Han et al [ 59 ] fabricated a sandwich-type porous GO/PI film in which GO contained porous FPI film located on both sides of a flat PI film via a facile breath figure method using flat PI film and GO contained FPI organic solution as substrate and casting solution, respectively. The results showed that with the addition of 0.5 wt.% GO/dimethyldioctadecylammonium bromide (DODA), the lowest dielectric constant of 2.21 at 10 MHz was achieved.…”
Section: Graphene Derivative/pi Composite Materialsmentioning
confidence: 99%